Investigation of two finite element modelling approaches for ballistic impact response of composite laminates. Issue 4 (4th July 2017) - Zhang, Xiaotian; Liu, Tao; He, Ningbo; Jia, Guanghui
ABSTRACT: We evaluated two numerical modelling methods based on different modelling scales in simulating the ballistic performance of composite laminates. An orthogonal continuous material model was developed and used to establish an equivalent macro-scale impact model of a projectile/composite target (uniform model). Combining the Chang–Chang failure model and tiebreak contact algorithm, the corresponding computational model for the cross-plied microstructure of composite laminates was constructed layer by layer (layered model). Using the two modelling methods mentioned earlier, a series of ballistic impact simulations were carried out for Kevlar/epoxy composite laminates, and the simulation results were compared with the corresponding experimental results. The computational capacities of the two methods were compared in terms of damage pattern, ballistic limit, residual velocity and computational efficiency. The results indicate that the uniform model can simulate the main ballistic impact behaviour of composite materials, whereas the layered model can simulate more detailed features of composite damage. Moreover, the predictive capability of the uniform model for ballistic limit and residual velocity is equivalent to that of the layered model, and the uniform model exhibits a higher computational efficiency than the layered model.